Development of B Cells and Erythrocytes Is Specifically Impaired by the Drug Celastrol in Mice - Kusy, Sophie; Ghosn, Eliver E. B.; Herzenberg, Leonore A.; Contag, Christopher H. (PLOS ONE, 2012)
Background Celastrol, an active compound extracted from the root of the Chinese medicine “Thunder of God Vine” (Tripterygium wilfordii), exhibits anticancer, antioxidant and anti-inflammatory activities, and interest in the therapeutic potential of celastrol is increasing. However, described side effects following treatment are significant and require investigation prior to initiating clinical trials. Here, we investigated the effects of celastrol on the adult murine hematopoietic system. Methodology/Principal Findings Animals were treated daily with celastrol over a four-day period and peripheral blood, bone marrow, spleen, and peritoneal cavity were harvested for cell phenotyping. Treated mice showed specific impairment of the development of B cells and erythrocytes in all tested organs. In bone marrow, these alterations were accompanied by decreases in populations of common lymphoid progenitors (CLP), common myeloid progenitors (CMP) and megakaryocyte-erythrocyte progenitors (MEP). Conclusions/Significance These results indicate that celastrol acts through regulators of adult hematopoiesis and could be used as a modulator of the hematopoietic system. These observations provide valuable information for further assessment prior to clinical trials.